A Core Physics Study of Advanced Sodium-Cooled TRU Burners with Thorium- and Uranium-Based Metallic Fuels. (1st May 2016) - You, Wuseung; Hong, Ser Gi
Abstract: In this work, 400-MW(electric) sodium-cooled fast reactor cores using thorium- and uranium-based metallic fuels for high burning rates of light water reactor spent-fuel transuranics (TRUs) are neutronically designed and analyzed based on equilibrium cycles with a focus on consistent comparative analysis of the differences in performance between thorium- and uranium-based fueled cores. Axial uranium and thorium blankets are introduced in thorium- and uranium-based driver fueled burner cores to improve TRU burning rates without considerable increases of burnup reactivity swing. For this core configuration, it was shown that cores using thorium and depleted uranium blankets can be designed to have a high TRU burning rate, a low sodium void reactivity (SVR) worth, and a low burnup reactivity swing. In particular, the use of uranium or thorium blankets without recycling in the thorium-based driver fueled cores led to significant reductions of burnup reactivity swing with considerable increases of the TRU burning rate and small increases of SVR. In addition, the core configuration having central nonfuel regions was considered to show the effects of the thorium-based driver metallic fuel versus the uranium-based metallic fuel coupled with moderator rods. The core configuration with thorium-based fuel led to a negative SVR without moderator rods, and the use of moderator rods further improved the Doppler coefficient and reduced SVR. Also, a decomposition analysis of SVR was performed to better understand the differences in the contributing factors between the uranium- and thorium-based fueled cores, and a quasi-static reactivity balance analysis was performed to show the inherent safety of the cores in terms of self-controllability.